PERAN TEKNOLOGI DALAM PENINGKATAN KAPASITAS SDM PESISIR - Nabila Zahratun Nisa; Tesa Cindita Br Nainggolan (Riset Sains dan Teknologi Kelautan, 2024)
This research explores the role of information and communication technology (ICT) in enhancing human resource capacity in coastal areas. The aim is to analyze how ICT has influenced education, training, productivity, and climate change adaptation in coastal regions. The research involves statistical data analysis on internet access and interviews with coastal residents.The results show that ICT has broadened access to education and training, facilitated global knowledge exchange, and provided more efficient reference resources. Technology also plays a role in improving productivity and climate change adaptation in coastal communities.In conclusion, ICT plays a crucial role in enhancing coastal human resource capacity. Collaboration among stakeholders is key to ensuring technology is used wisely in sustainable planning and management. Keywords: information and communication technology, coastal areas, education, climate change, human resource capacity.